Performance of Takakura composting method in the decentralised composting center and its comparative study on environmental and economic impacts in Bandung city, Indonesia - Kohei Hibino; Koji Takakura; Sudarmanto Nugroho; Ryoko Nakano; Ria Ismaria; Tati Haryati; Deti Yulianti; Eric Zusman; Junichi Fujino; Junko Akagi (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Takakura Composting Method (TCM) is a simple and cost-effective aerobic composting method using locally available materials and has been widely introduced in Indonesia and other countries. This study tracked the progress of scaling the TCM up to 1 tonne/day of organic waste input at the decentralised composting centre in Bandung City, Indonesia. A comparative study was conducted to assess the environmental and economic impacts by using the performance data of TCM.Method A combination of Life Cycle Assessment and Cost-Benefit Analysis were performed to compare the net greenhouse gas (GHG) emissions and Net Present Value (NPV) of six different municipal solid waste treatment scenarios to treat 1 tonne of food waste. The impacts were also assessed between different system boundaries with or without compost use, and by applying different emission factors for composting to the static windrow and TCM.Results  Home composting showed the least GHG emissions (-601 kg CO2-eq/t) and highest NPV (Indonesian Rupiahs (IDR) 518,790/tonne) and is thus suggested to be the most favourable option. While the least favourable options were either landfilling which showed the highest GHG emissions (628 kg CO2-eq/t), or incineration which showed the lowest NPV (IDR -818,373/tonne).Conclusion As the home composting was not considered to be a realistic option for wide application, a combination of one large centralised composting centre and a small decentralised composting centre in each sub-district is suggested in the case of Bandung City.